Maintaining diversity of integrated rice and fish production confers adaptability of food systems to global change - Freed, S.; Barman, B.; Dubois, Mark; Flor, R. J.; Funge-Smith, S.; Gregory, R.; Hadi, B. A. R.; Halwart, M.; Haque, M.; Jagadish, S.V. Krishna; Joffre, Olivier M.; Karim, M.; et al. (Frontiers Media, 2020)
Rice and fish are preferred foods, critical for healthy and nutritious diets, and provide the foundations of local and national economies across Asia. Although transformations, or “revolutions,” in agriculture and aquaculture over the past half-century have primarily relied upon intensified monoculture to increase rice and fish production, agroecological approaches that support biodiversity and utilize natural processes are particularly relevant for achieving a transformation toward food systems with more inclusive, nutrition-sensitive, and ecologically sound outcomes. Rice and fish production are frequently integrated within the same physical, temporal, and social spaces, with substantial variation amongst the types of production practice and their extent. In Cambodia, rice field fisheries that strongly rely upon natural processes persist in up to 80% of rice farmland, whereas more input and infrastructure dependent rice-shrimp culture is expanding within the rice farmland of Vietnam. We demonstrate how a diverse suite of integrated production practices contribute to sustainable and nutrition-sensitive food systems policy, research, and practice. We first develop a typology of integrated production practices illustrating the nature and degree of: (a) fish stocking, (b) water management, (c) use of synthetic inputs, and (d) institutions that control access to fish. Second, we summarize recent research and innovations that have improved the performance of each type of practice. Third, we synthesize data on the prevalence, outcomes, and trajectories of these practices in four South and Southeast Asian countries that rely heavily on fish and rice for food and nutrition security. Focusing on changes since the food systems transformation brought about by the Green Revolution, we illustrate how integrated production practices continue to serve a variety of objectives to varying degrees: food and nutrition security, rural livelihood diversification and income improvement, and biodiversity conservation. Five shifts to support contemporary food system transformations [i.e., disaggregating (1) production practices and (2) objectives, (3) utilizing diverse metrics, (4) valuing emergent, place-based innovation, (5) building adaptive capacity] would accelerate progress toward Sustainable Development Goal 2, specifically through ensuring ecosystem maintenance, sustainable food production, and resilient agricultural practices with the capacity to adapt to global change.